Direction of trade statistics yearbook 2010 - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2010)
Reports the values of imports and exports from 184 advanced and developing countries from 2003 to 2009.
rpm 23/05/13
Ref
Keywords: International trade; Commercial statistics